1996
DOI: 10.1136/ard.55.7.424
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular hyaluronan injections in the treatment of osteoarthritis of the knee: a randomised, double blind, placebo controlled multicentre trial. Hyaluronan Multicentre Trial Group.

Abstract: Objective-To assess the effects of intraarticular injections of hyaluronan on symptoms ofknee osteoardtritis (OA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(133 citation statements)
references
References 25 publications
7
120
1
5
Order By: Relevance
“…29 In clinical practice, however, intraarticular HA injection is well tolerated, and no adverse effects have been reported in most previous studies. [12][13][14][15][30][31][32] Different sets of experiments will be required to confirm our data and verify our working hypothesis.…”
Section: Effects Of Hyaluronic Acid In Rotator Cuff Diseasementioning
confidence: 93%
See 2 more Smart Citations
“…29 In clinical practice, however, intraarticular HA injection is well tolerated, and no adverse effects have been reported in most previous studies. [12][13][14][15][30][31][32] Different sets of experiments will be required to confirm our data and verify our working hypothesis.…”
Section: Effects Of Hyaluronic Acid In Rotator Cuff Diseasementioning
confidence: 93%
“…Although HA is widely used in the treatment of OA, [12][13][14] the nature of its anti-inflammatory mechanism remains poorly understood. 11 Similarly, a clinical benefit of HA in rotator cuff disease was demonstrated by Shibata et al, 15 although little is known about its anti-inflammatory effect in the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One early placebo-controlled trial indicated increased benefit among older patients with more significant osteoarthritis. (Lohmander et al, 1996) In another study, Dahlberg et al evaluated a group of patients with normal radiographs and early arthritic changes observed at arthroscopy. They reported no significant benefit from 5 weekly injections of sodium hyaluronate (compared with placebo) (Dahlberg et al, 1994).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…This is one of the main reasons why intra-articular HA injection has been widely accepted as a treatment of OA (Goldberg and Buckwalter 2005). Practically, many clinical investigations of HA injections showed the efficacy on symptoms of OA patients (Lohmander et al 1996;Altman and Moskowitz 1998;Brandt et al 2001). Joint immobilization is an essential treatment in daily examinations to decrease pain and joint damage (Salter and Field 1960;Trudel et al 2000), but it also causes degeneration or atrophy of the articular cartilage (Trudel et al 2005).…”
Section: Animalsmentioning
confidence: 99%